The relationship between negative workplace gossip and thriving at work among Chinese kindergarten teachers: the roles of psychological contract breach and bianzhi - He, Can; Feng, Tongtong; Xiong, Jie; Wei, Hua (Frontiers in Psychology, 2023)
Introduction Exploring the influencing factors and functioning mechanisms of thriving at work is of practical significance both for teachers and kindergartens. Based on the socially embedded model of thriving at work, this study aimed to examine the association between negative workplace gossip and thriving at work. The mediating role of psychological contract breach and the moderating role of bianzhi were also examined. Methods A total of 1105 Chinese kindergarten teachers were chosen to complete a questionnaire on negative workplace gossip, psychological contract breach, and thriving at work. Results The results demonstrated that negative workplace gossip was positively associated with psychological contract breach and negatively associated with thriving at work. In addition, psychological contract breach was negatively associated with thriving at work. According to the mediation model test, psychological contract breach was a mediating factor between negative workplace gossip and thriving at work. The impact of psychological contract breach on thriving at work could be further moderated by bianzhi. Conclusion This study complements knowledge systems about the influential factors and functional mechanisms of thriving at work. In practical terms, this study offers a fresh and innovative perspective for kindergartens seeking to enhance teachers’ thriving at work.